Ionizing photon production and escape fractions during cosmic reionization in the TNG50 simulation - Kostyuk, Ivan; Nelson, Dylan; Ciardi, Benedetta; Glatzle, Martin; Pillepich, Annalisa (Monthly notices of the Royal Astronomical Society, 2023)
In this work, we investigate the dependence of the escape fraction of ionizing photons, fesc, on various galaxy and host halo properties during the epoch of reionization. We post-process the TNG50 magnetohydrodynamical simulation from the IllustrisTNG project using the three-dimensional multifrequency radiative transfer code CRASH. Our work covers the stellar mass range of 106 ≲ M⋆/M⊙ ≲ 108 at redshifts 6 < z < 10. Adopting an unresolved, cloud-scale escape fraction parameter of unity, the average halo escape fraction fesc increases with mass from ∼0.3 at M⋆ = 106 M⊙ to ∼0.6 at M⋆ = 107.5 M⊙, after which we find hints of a turnover and decreasing escape fractions for even more massive galaxies. However, we demonstrate a strong and non-linear dependence of fesc on the adopted subgrid escape fraction, resulting in uncertainties for the absolute value of the escape fraction. In addition, fesc has significant scatter at fixed mass, driven by diversity in the ionizing photon rate together with a complex relationship between (stellar) source positions and the underling density distribution. The global emissivity is consistent with observations for reasonable cloud-scale absorption values, and haloes with a stellar mass ≲107.5 M⊙ contribute the majority of escaping ionizing photons at all redshifts. Incorporating dust reduces fesc by a few per cent at M⋆ ≲ 106.5 M⊙, and up to 10 per cent for larger haloes. Our multifrequency approach shows that fesc depends on photon energy, and is reduced substantially at E > 54.4 eV versus lower energies. This suggests that the impact of high-energy photons from binary stars is reduced when accounting for an energy-dependent escape fraction.
Veröffentlicht: 17. März 2023
Gesehen am 14.08.2024